PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA MATERI POKOK SEL DI KELAS XI SMA NEGERI 1 BATANG ONANG - Riki Rinaldi Rinaldi (Jurnal Education and Development, 2018)
The aims of this study is to see the effect cooperative type of think pare share on students’ learning achievement of Biology on cell matter to the XI grade students of SMA Negeri 1 Batang Onang. The population of the study was all the XI-science grade students, there are two parallel classes. It consists of 58 students. Cluster random sampling technique was applied in this research. The sample of the research was two classes of science classes. XI-science 1 was a experimental group and XI-science 2 was a control group. Based on analysis of the descriptive data, the pretest of experimental group was 41.5 in “fell” category, while in posttest was 72.8 in “good” category. In control group, the students achievement on pretest was 38.7 in “fell” category, while in posttest the average score was “less” category. Based on the data analysis, the researcher found that ttest was 3.96 and ttable was 1.70. In other words, the hypothesis of this research was accepted. It means, there is the significant effect of cooperative type of think pare share on students’ learning achievement of Biology on cell matter to the XI grade students of SMA Negeri 1 Batang Onang.